Pemetaan Landuse Skala RW di Desa Cikeusik Kabupaten Pandeglang Provinsi Banten - Yundrawan Ega Wibowo; Sutoyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Boundaries of the village is the boundary of government administration between villages which is a series of coordinate points that are on the surface of the earth can be signs of nature such as mountains, rivers or artificial elements (roads, railroads, channels Irrigation, and boundary pillars) in the form of maps. The process of mapping the RW scale landuse in Cikesik village is done in two stages, namely the observation phase and map making stage. The observation phase is conducted for three days starting from 7 – 10 June 2019, observation is done to ensure the boundaries and potential of village in Ciagic village. The map making phase was conducted on 11 – 20 June 2019. The area of Ciagic village with scale mapping method Ciagic village is dominated by rice fields. The area covered as a tree of 47.15 hectares, a residential area of 18.95 ha, and a paddy field area of 56.73 ha differs from the area of Ciarate village, which is calculated through the RW scale mapping calculation method. The village scale mapping method gained an area of 697.31 hectares for trees, 79.72 hectares for settlements, and 572.05 ha for paddy fields. The Total area of Ciagic village has an area of 1,349.09 ha. Keywords: map, scale, spacious